2023
DOI: 10.3389/fnut.2023.1230747
|View full text |Cite
|
Sign up to set email alerts
|

Association between the dietary inflammatory index and markers of endothelial and systemic inflammation in hemodialysis patients

Arman Arab,
Elham Karimi,
Maryam Nazari
et al.

Abstract: ObjectivesThe current survey aimed to investigate the link between energy-adjusted dietary inflammatory index (E-DII) and risk factors for CVD including markers of endothelial and systemic inflammation in Iranian hemodialysis patients.MethodsPatients on hemodialysis for at least 6 months prior to enrollment were considered eligible in this cross-sectional study. The usual dietary intakes of the hemodialysis individuals were examined through 4 non-consecutive days including 2 dialysis days and 2 non-dialysis da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
0
1
Order By: Relevance
“…Thus, in the present study, higher protein intakes of participants with the highest DAL scores may also be due to higher intakes of whey protein, which could result in higher level of inflammatory biomarkers. However, a pilot study on 14 chronic HD patients aged 16-71 years showed that red meat snacks (27 grams of protein per day) for 30 days did not affect CRP levels in these patients (23). The discrepancy found with the current study could be related to the differences in the study design, study population, and various potential covariates.…”
Section: Discussioncontrasting
confidence: 89%
“…Thus, in the present study, higher protein intakes of participants with the highest DAL scores may also be due to higher intakes of whey protein, which could result in higher level of inflammatory biomarkers. However, a pilot study on 14 chronic HD patients aged 16-71 years showed that red meat snacks (27 grams of protein per day) for 30 days did not affect CRP levels in these patients (23). The discrepancy found with the current study could be related to the differences in the study design, study population, and various potential covariates.…”
Section: Discussioncontrasting
confidence: 89%